2011
DOI: 10.1097/ta.0b013e31822e2823
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Flap Reconstruction With Vacuum-Assisted Closure Management of the Open IIIB Tibial Fracture

Abstract: The VAC therapy may help to reduce the flap size and need for a flap transfer for type IIIB open tibial fractures. However, prolonged periods of VAC usage, greater than 7 days, should be avoided to reduce higher infection and amputation risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 22 publications
4
87
0
3
Order By: Relevance
“…Pediatric studies were not excluded. Thirteen studies remained [6,7,15,16,29,30,33,35,36,45,47,49,50] after reading the abstract and the full-length article as needed to ascertain data points. Twenty-two studies were eliminated from the final 35 articles identified because they were review articles (n = 8), articles regarding pilon fracture (n = 2), and articles with insufficient data or case reports (n = 12).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…Pediatric studies were not excluded. Thirteen studies remained [6,7,15,16,29,30,33,35,36,45,47,49,50] after reading the abstract and the full-length article as needed to ascertain data points. Twenty-two studies were eliminated from the final 35 articles identified because they were review articles (n = 8), articles regarding pilon fracture (n = 2), and articles with insufficient data or case reports (n = 12).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…All publications were from 2006 and later, likely owing to FDA approval in 1997 and several years thereafter for clinicians to use negative pressure wound therapy and several more years for patient followup. One of the 13 studies was an RCT [49], and the remaining 12 were retrospective [6,7,15,16,29,30,33,35,36,45,47,50]. The RCT was not eliminated because of lack of study quality as defined by Moher et al [37] or by Detsky et al [17].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 3 more Smart Citations